Efektivitas Edukasi dan Latihan Pertolongan Pertama Pada Kecelakaan (P3K) Untuk Meningkatkan Ketrampilan Ekstrakurikuler PMR Di SMK Ahmad Yani Gurah - Heni, Sutiyah (Akademi Keperawatan Husada Karya Jaya Jakarta, 2025)
First Aid in Accidents (P3K) is very important to implement, as quick and precise actions can save lives, prevent further injuries, and accelerate the healing process of victims. Having knowledge about First Aid in Accidents enables individuals to provide critical initial assistance before professional medical help arrives and can reduce the risk of serious complications. Education and training in First Aid in Accidents (P3K) are among the interventions to enhance the knowledge and skills of members of the Red Cross Youth (PMR) in schools. Training on First Aid in Accidents (P3K) is conducted for students participating in extracurricular activities of the Red Cross Youth (PMR) at school. The aim is to determine the effectiveness of First Aid in Accidents (P3K) training for improving extracurricular skills of PMR At SMK Ahmad Yani Gurah. This research design is quasi-experimental with one group pre-test and post-test, involving a sample size of 31. The sampling technique used is total sampling. The research instrument employs a questionnaire and checklist. Data analysis is conducted using the paired t-test. The results indicate that the p-value is 0.001 (<0.005), thus Ha is accepted, indicating that providing education and training in P3K can improve first aid skills among student members of PMR at school.